Evaluation of the clinical application of histamine H2 receptor antagonists in the prevention of chemotherapy-induced nausea and vomiting based on the attribute hierarchy model method - Song, Jiawei; Liu, Li; Meng, Bingbing; Zhao, Huanhuan; Zhang, Pengcheng; Chen, Huijuan; Wang, Yuanyuan (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate the clinical application of histamine H2 receptor antagonists (H2 RAs) in the prevention of chemotherapy-induced nausea and vomiting (CINV), focusing on the rationality of H2 RAs use, the utilization rates and costs of different H2 RAs agents, to provide a reference for the rational use of H2 RAs in this context.MethodsEvaluation criteria for the rational use of H2 RAs in CINV prevention were established based on domestic and international drug package inserts, clinical guidelines, and national expert consensus. A retrospective study was conducted, and the rationality of H2 RA use in CINV prevention was analyzed and evaluated using the Attribute Hierarchy Model (AHM) method among 323 patients discharged from the People’s Hospital of Bozhou in April 2024. The clinical application of different H2 RAs was analyzed.ResultsThe significant issues of irrational use of H2 RAs in CINV prevention included inappropriate solvent and incompatibility (71.83%), use without indications (70.59%), inappropriate dosage and administration (45.82%), prolonged duration of therapy (30.65%), lack of laboratory monitoring (24.46%), and unreasonable efficacy evaluation (23.84%). The mean case score was 71.03 ± 11.06, with oncology cases scoring 70.16 ± 11.03 and non-oncology cases scoring 74.81 ± 10.44, indicating a statistically significant difference (P < 0.01). The mean cost of H2 RAs in CINV prevention was 114.46 ± 132.64 yuan, accounting for 2.72% of the mean total drug expenditure. Specifically, the average price of H2 RAs was 123.09 ± 139.45 yuan in oncology cases and 70.89 ± 84.64 yuan in non-oncology cases, also with a statistically significant difference (P < 0.01). The clinical application of H2 RAs showed a preference for the higher-priced ranitidine (88.54%).ConclusionH2 RAs remain widely used in the prevention of CINV; however, the majority of cases (98.45%) demonstrated irrational use, particularly prophylactic administration without appropriate indications. The rationality of H2 RAs use in oncology departments was lower than that in non-oncology departments, while the associated drug costs were higher. Strengthened management of H2 RAs application in CINV prevention is needed to improve the rationality of drug use and to ensure safety, efficacy, and cost-effectiveness for patients.